Analisis Pengaruh Tingkat Pengangguran dan Tingkat Kemiskinan Terhadap Pertumbuhan Ekonomi Provinsi Jawa Tengah Tahun 2012-2021 - Artiza, Shafira; Meliza, Rizqa; Desmawan, Deris (Jurnal Manajemen Akuntansi (JUMSI), 2022)
Several indicators to assess the economy in a region, economic growth is one of the indicators. However, to achieve good economic growth has many aspects that must be improved by the local government. Poverty and unemployment are two things that have an influence on economic growth. The purpose of this study is so that we know to what extent the effect of unemployment and poverty on economic growth in Central Java Province in 2012-2021. Data were taken from Central Java BPS using multiple linear regression analysis with the help of SPSS application.